Patient and regimen characteristics associated with self-reported nonadherence to antiretroviral therapy. - Patrick S Sullivan; Michael L Campsmith; Glenn V Nakamura; Elin B Begley; Jeffrey Schulden; Allyn K Nakashima (PLoS ONE, 2007)
BACKGROUND: Nonadherence to antiretroviral therapy (ARVT) is an important behavioral determinant of the success of ARVT. Nonadherence may lead to virological failure, and increases the risk of development of drug resistance. Understanding the prevalence of nonadherence and associated factors is important to inform secondary HIV prevention efforts. METHODOLOGY/PRINCIPAL FINDINGS: We used data from a cross-sectional interview study of persons with HIV conducted in 18 U.S. states from 2000-2004. We calculated the proportion of nonadherent respondents (took <95% of prescribed doses in the past 48 hours), and the proportion of doses missed. We used multivariate logistic regression to describe factors associated with nonadherence. Nine hundred and fifty-eight (16%) of 5,887 respondents reported nonadherence. Nonadherence was significantly (p<0.05) associated with black race and Hispanic ethnicity; age <40 years; alcohol or crack use in the prior 12 months; being prescribed >or=4 medications; living in a shelter or on the street; and feeling "blue" >or=14 of the past 30 days. We found weaker associations with having both male-male sex and injection drug use risks for HIV acquisition; being prescribed ARVT for >or=21 months; and being prescribed a protease inhibitor (PI)-based regimen not boosted with ritonavir. The median proportion of doses missed was 50%. The most common reasons for missing doses were forgetting and side effects. CONCLUSIONS/SIGNIFICANCE: Self-reported recent nonadherence was high in our study. Our data support increased emphasis on adherence in clinical settings, and additional research on how providers and patients can overcome barriers to adherence.